Physical activity and sedentary behavior during the early years in Canada: a cross-sectional study - Colley, Rachel C; Garriguet, Didier; Adamo, Kristi B; Carson, Valerie; Janssen, Ian; Timmons, Brian W; Tremblay, Mark S (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Physical activity and sedentary behavior habits are established during early childhood, yet only recently has objectively measured data been available on children aged 5 years and younger. This study presents data on the physical activity and sedentary behaviors of Canadian children aged 3–5 years. Methods Data were collected as part of the Canadian Health Measures Survey between 2009 and 2011. A nationally-representative sample (n = 459) of children aged 3–5 years wore Actical accelerometers during their waking hours for 7 consecutive days. Data were collected in 60-sec epochs and respondents with ≥4 valid days were retained for analysis. Parents reported their child’s physical activity and screen time habits in a questionnaire. Results Eighty-four percent of 3–4 year old children met the physical activity guideline of 180 minutes of total physical activity every day while 18% met the screen time target of <1 hour per day. Fourteen percent of 5 year old children met the physical activity guideline of 60 minutes of daily moderate-to-vigorous physical activity (MVPA) while 81% met the screen time target of <2 hours per day. Children aged 3–4 years accumulated an average of 352 min/d of total physical activity and 66 minutes of MVPA while 5 year old children accumulated an average of 342 min/d of total physical activity and 68 minutes of MVPA. Children were sedentary for approximately half of their waking hours and spent an average of 2 hours per day in front of screens. Only 15% of 3–4 year olds and 5% of 5 year olds are meeting both the physical activity and sedentary behavior guidelines. Conclusions Promoting physical activity while reducing sedentary behavior is important at all stages of life. The findings of the present study indicate that there remains significant room for improvement in these behaviors among young Canadian children.